Pendampingan Pekerjaan Peninggian Jalan Anang Sya’rani Sebagai Upaya Penanggulangan Banjir Di Wilayah Rawan Genangan Di Kabupaten Banjar - Arifin; Ahmad Riduan; Elva Shanty Widuri; Misnawati; Trie Rezky Novianti; Muhammad Chandra; Hafiz Abdullah Nor Fajar (CV. SINAR HOWUHOWU, 2025)
Anang Sya’rani Street in Martapura Timur Subdistrict, Banjar Regency, serves as a vital access route for community activities in the areas of economy, social interaction, and religious tourism, particularly for pilgrims visiting local religious sites. However, this road frequently experiences flooding during the rainy season due to its low elevation, which disrupts mobility and accelerates road surface damage. To address these issues, a community service initiative was carried out involving the elevation and improvement of the road using a technical approach. This included the installation of a Lower Base Course (LPB), Upper Base Course (LPA), asphalt paving using Hot Rolled Sheet–Wearing Course (HRS-WC), and concrete casting of road shoulders to ensure structural stability. The activity was conducted over a two-month period, with strict supervision on material quality, final elevation levels, and occupational safety compliance. Evaluation results indicate a significant improvement in the road’s resistance to water inundation, along with positive feedback from local residents. This road elevation effort has proven to be an effective solution in enhancing public mobility and improving the sustainability of local infrastructure.